(untitled) (Research, Society and Development, 2021)
The anthropogenic factors such as displacement of populations, agglomerations and the accelerated and precarious process of urbanization in line with climatic factors create conditions for the rapid increase in communicable diseases, especially those of infectious origin. This study corroborates the idea that weather variations can cause undesirable effectsabout the healthy state of man, in direct and / or indirect format. The purpose of this review was to investigate and analyze the studies in the literature about the relationship betweenclimatic variantsand diseases of infectious origin. Its about a review qualitative, descriptive bibliography, such as Integrative Literature Review, based on scientific investigations disclosed between 2015 to 2020. Andfetched searchesin the databases: SciELO, LILACS and MEDLINE. Collection of studieswas put to a form instrument authenticated by Ursi and Galvão (2015) Adapted. For analysis of information, Bardin Thematic Content Analysis (ACTB) was used. A total of 220 publications were identified, 203 in MEDLINE, 14 in LILACS and 03 in SciELO. Final sample was 13 productions.O quantitative Brazilian research on the theme was lower than expected, which is able toperhaps justified by the choice of keywords. Temperature, humidity, anthropogenic intervention, among others, alter or influence in some way the spread of this infection, this turns onwarning for the importance of a approximation inter and multidisciplinarybut leaving a sustainable and fair ethical perspective that allows dignified and balanced coexistence with all living beings.